REVENUES AS A KEY FACTOR FOR MEETING THE HOUSEHOLD FOOD INTERESTS: STATUS AND FACTORS OF IMPACT (INNOVATIVE ECONOMY, 2020)
Nyzhnyk I.O. REVENUES AS A KEY FACTOR FOR MEETING THE HOUSEHOLD FOOD INTERESTS: STATUS AND FACTORS OF IMPACTPurpose. The aim of the article is identification of the sources of income that have the greatest impact on food costs in the structure of total household expenditure and factors that influence the formation of household income.Methodology of research. General scientific and special methods are used in the process of research, in particular: the method of correlation and regression analysis - to determine the sources of income that have the greatest impact on food expenditure in the structure of total household expenses, and the establishment of a tight relationship between the growth of real GDP and wage increases hired workers in Ukraine and abroad; the monographic method and the method of comparison are used to determine the factors that influence the formation of household incomes.Findings. It is established that the growth of employment, income, including through state aid, increases the level of economic availability of food. It was found that in the structure of income of the population the most important source is the payment of labor, the share, which varies in the direction of reduction from 52 to 47%. This indicates a reduction of labor motivation of the economically active population of Ukraine to find work in the country and its reorientation to the foreign labor market.It is suggested that the reason for the reduction of the share of household income from entrepreneurship and self-employment is the stable unfavorable conditions for entrepreneurial activity. The main reasons for the low income level of Ukrainian households, including wages, are substantiated. An unfair distribution of national income and a low level of labor productivity have been identified. It is established that the given negative is the basis of formation of an atmosphere of despair in the society in the self-power, education of paternalistic mood and marginalization of a significant part of the population.Originality. The quantitative parameters of the connection between the share of food expenses in the structure of total household expenses and the employment of the population, between the volume of its total resources, the dynamics of food production, the size of the allocated subsidy and the state social assistance to the poor are specified. For the first time, a quantitative comparative analysis of the link between the growth of real GDP and the increase in wages in Ukraine and the EU countries with the highest level of the shadow economy was conducted, which allowed to confirm the assumption of unfair distribution of national income in Ukraine.Practical value. The obtained results of the conducted research provide an opportunity to improve the methodology of analysis of factors influencing the formation and use of incomes of the population, and promote the development of the state system of social protection in the part of programs of food aid to the poor.Key words: food interest, satisfaction, incomes, low income, employment, subsidies, social protection, wages, distribution of national income, labor productivity.
Keywords: Key words; food interest; satisfaction; incomes; low income; employment; subsidies; social protection; wages; distribution of national income; labor productivity.